A case report of primary amebic meningoencephalitis in North Florida. (2021) - Anjum, Saad K.; Mangrola, Karna; Fitzpatrick, Garrett; Stockdale, Kimberly; Matthias, Laura; Ali, Ibne Karim M.; Cope, Jennifer R.; O'Laughlin, Kevin; Collins, Shelley; Beal, Stacy G.; Saccoccio, Frances M.
Abstract: Primary amebic meningoencephalitis is a rare, usually fatal disease, caused by Naegleria fowleri . This case highlights the challenging clinicopathologic diagnosis in a 13-year-old boy who swam in freshwater in northern Florida where a previous case had exposure to a body of water on the same property in 2009.